Impact of irrigation participation on households food security in a rural area of Ethiopia: application of propensity score matching (PSM) method for causal inference - Ebrahim, Endris Assen; Toy, Ahmet (Frontiers in Sustainable Food Systems, 2024)
Irrigation plays an imperative role in the expansion of agriculture production and productivity growth that reduces food security. Implementing irrigation schemes is a crucial step towards ending poverty and enhancing food security. A strong association between farmers' engagement in irrigated agriculture boosts households' annual income and food expenditure and improves households' food security. To what extent, though, does the households' food security in the Dessie Zuria District that employs irrigation surpass the food security of other households that rely on rainfall remains unclear.In addition, there is not enough information available in the research area about how irrigation affects household income or expenditure and food security. Thus, this study aims to assess the factors influencing households' participation in small-scale irrigation and the effect of irrigation on food security. This study covers the severity of the issue and closes any gaps. Multistage random sampling was used to consider the proportion of the heterogeneous groups to the entire population. The data were gathered in 2023 at Dessie Zuria District from a survey of 198 households (92 small-scale irrigation users and 106 non-users). Utilizing the logistic regression model, the variables affecting the likelihood of small-scale irrigation engagement were examined. Propensity Score Matching was used to examine the impacts of small-scale irrigation on households' food security using the household's annual income and their annual food expenditure as proxy variables. Eleven explanatory variables were used and a logit analysis result showed household family size, livestock holding in total livestock unit, access to credit, sex of households, and cultivable land were found as the main factors of smallscale irrigation participation. The Propensity Score Matching model result indicates that the adoption of small-scale irrigation increases the average annual income and annual food expenditure by 60, 273.27 (54.88%) and 5,589.12 (55.31%) Ethiopian Birr, respectively. Therefore, to recover the food security of agricultural households' current situation stakeholders should give due attention to the growth of small-scale irrigation.